Risk-Induced Foraging Behavior in a Free-Living Small Mammal Depends on the Interactive Effects of Habitat, Refuge Availability, and Predator Type - Kelleher, Victoria; Hunnick, Louis; Sheriff, Michael J. (Frontiers in Ecology and Evolution, 2021)
Predators have a major influence on prey populations and broader ecosystem dynamics through both their consumptive and non-consumptive effects. Prey employ risk-induced trait responses such as shifts in habitat use or changes in foraging behavior in response to the presence of predators. Risk-induced changes in foraging depend upon both the predator community and the environmental context; however, the influence of these factors have rarely been concurrently examined in free-living animals. We investigated the interactive effects of habitat, refuge availability, and predator type on the foraging behavior of free-living white-footed mice, accounting for the abiotic factor moonlight. We used auditory calls of a local terrestrial cursorial predator and a local avian ambush predator to simulate predation risk in both a forest edge and a forest interior habitat, and measured the foraging of mice under different experimental refuge types. We found that, while mice generally had reduced foraging when exposed to predation risk, the degree of this response depended on an interaction among habitat, refuge use, and type of predator. Prey had the greatest reduction in foraging and used refuges the most when exposed to cursorial-hunting foxes at the open forest edge. The risk-induced reduction in foraging and the use of refuges was much weaker in the forest interior, but even here foxes elicited a greater response as compared to owls. Generally, foraging tended to decrease with increasing moonlight, but this was not significant. We suggest that it is the temporal nature of cursorial vs. ambush predators in our system that drives such effects as opposed to their hunting mode, and that prey responses to temporal hotspots of risk need further examination. Generally, our results show that wild small-mammal prey species have variable responses to predation risk depending on the environmental context.